IMPLEMENTASI NILAI RELIGIUS MELALUI BUDAYA SEKOLAH: STUDI FENOMENOLOGI - Framz Hardiansyah; Mas'odi Mas'odi (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2020)
Religious value inculcation is an awareness and planned to prepare students in terms of knowing, and understanding, and living, practice so that it arises to believe in the religion they profess. Based on the above understanding, the authors are interested in conducting research on the implementation of religious values ​​through school culture. This research focuses on: (1) What forms of religious values ​​in primary schools, (2) How do the implementation of religious values ​​through school culture. With the aim of: (1) To find out the form of religious culture in elementary schools, (2) To find out the implementation of religious values ​​through school culture. In this research the method used is qualitative phenomenology through case studies. Data collection techniques in this study were conducted by (1) semitructured interviews, (2) unstructured observations, (3) documentation, so that the results are arranged systematically, the authors step in analyzing data is to use data reduction, data presentation and data verification (drawing conclusions) . The results of this study indicate (1) the form of religious values ​​in SDN Baban 1 Sumenep include: (a) the value of aqidah / worship consisting of praying in congregation, reading prayer, reading Al Quran short letters, (b) moral values ​​consisting of politeness, 3S (smile, greetings, greetings), silaturrahim values ​​(c) shari'ah values ​​consist of disciplinary values ​​and social values, (2) implementation of religious values ​​through school culture in SDN Baban 1 Sumenep include: (a) routine activities, (b) routine activities, (b) ) spontaneous activities, (c) conditioning, (d) exemplary.